Dynamic Changes in Volatile Flavor Components during Enzymatic Hydrolysis of Walnut (Juglans regia L.) Protein - Kai LI; Yuchuan FAN; Lan DING; Ming ZENG; Hao SONG (Shipin gongye ke-ji, 2022)
In order to study the dynamic changes in volatile flavor components of walnut (Juglans regia L.) protein during enzymatic hydrolysis, single-enzyme hydrolysis was carried out using Protamex® protease. The headspace solid-phase microextraction and gas chromatography-mass spectrometry were used to analyze the volatile chemical components of the enzymatic hydrolysis solution at different time points, and the results were used to carried out relative odor activity analysis and principal component analysis (PCA). The results showed that fifty-five and sixty-eight aroma substances were detected before and after enzymolysis, including aldehydes, alcohols, ketones, esters and furans. With the progress of enzymatic hydrolysis, the key aroma components were gradually transformed from twenty-one compounds such as n-valeraldehyde, 1-octene-3-ol and isovaleraldehyde before enzymolysis into thirteen compounds such as isovaleraldehyde, dimethyl disulfide and (2E,4E)-decadienal. The PCA results showed that the aroma characteristics tended to be stable after enzymatic hydrolysis for 3 h, in addition, the aroma structure change of the enzymatic hydrolysis solution was mainly affected by the concentration change of 2-ethyl-1-hexanol, 2-ethyl furan, (2E,4E)-decadienal, 2-pentyl furan, (Z)-4-heptenal and dimethyl disulfide. These research results would provide a theoretical basis for the control of flavor quality during the preparation of walnut peptides by enzymolysis.